Socialization of health protocols in the new habit era of the Covid-19 pandemic to build a positive response of the community in Kapanewon Sleman - Naris Dyah Prasetyawati; Sigid Sudaryanto; Tri Mulyaningsih; Muslikah Muslikah; Wahyu Widyantoro (Community Empowerment, 2022)
Public perception in dealing with the Covid-19 pandemic is still divided into two groups, negative and positive stigmas. Strengthening of information and education to the individual level about the importance of implementing health protocols must always be carried out. Support from various parties is also needed so that the obligation to prevent the transmission of Covid-19 is not only the responsibility of certain parties. This activity aims to educate the public in implementing health protocols in all their activities. After the program, it was found that there was an increase in the knowledge, attitudes and behavior of the participants after participating in the activity. In addition, as many as 100% of the participants were enthusiastic about the activities that had been carried out and expressed their willingness to take part in activities that would be held on another occasion.